SRU/W‐based CRIS systems search profile. Issue 2 (2014) - Valentin Penca; Siniša Nikolić; Dragan Ivanović; Zora Konjović; Dušan Surla
<x xml:space="preserve"> Abstract </x> Purpose – The main aim of this paper is to develop a CRIS systems search profile that would enable CRIS users to perform unified and semantically rich search for the records stored in the CRIS systems. Design/methodology/approach – Prior to the search profile construction, diverse representative types of the scientific research data store systems (CRISs, digital libraries, institutional repositories, and search portals) were analyzed versus available search modes, indexes and query types. Findings – The new SRU/W standard based search profile (CRIS profile) for the purpose of searching scientific research data was proposed, that supports search for all types of data identified through an exhaustive analysis covering all major scientific and research data store systems. Research limitations/implications – Constraints of the proposed profile could appear from the fact that data identified in analyzed systems do not comprise all scientific research data recognized by CERIF standard which, in turn, could call for the profile extension. Practical implications – Search profile has been verified on the data in the existing CRIS systems at the University of Novi Sad. The CRIS search profile enables unified and semantically rich search for the data stored in heterogeneous distributed scientific research data store systems. Originality/value – The new SRU/W‐based search profile extensively supports the search domain of scientific research data in CRIS systems. Commitments to SRU/W and CQL standards enable interoperability among heterogeneous, distributed scientific research data sources. <ack> <x xml:space="preserve"> Acknowledgements </x> Results presented in this paper are part of the research conducted within the Grant No. III‐47003, Ministry of Science and Technological Development of the Republic of Serbia. </ack>